Isolation and Characterisation of Thionin Genes in Rice (Oryza Sativa) - Jason, Chiew (2001)
Thionins are cysteine rich, basic and toxic proteins that are assumed to be involved in the defense against pathogens. Two partial cDNA clones encoding for putative thionin in rice were isolated from endosperm (Rth-l) and shoots (Rth-2). The nucleotide sequences encoding for thionin precursor were further identified from the amplification of the 3' -end of the cDNA. The amino acid sequence for JRth-l isolated from endosperm showed 72% homology to barley leaf thionins DB4 (Bohlmann and Apel, 1987), 68% to pKG1940 (Gausing, 1987), 51% to hordothionin Hth-1 (Rodriguez-Palenzuela et 01., 1988), 50% to purothionin Pur-AI (Ohtani et 01., 1977), 33% to crambin Thi2Ca1 (Teeter et 01., 1981) and viscotoxin Vis A3 (Samuelsson et 01., 1974). The homologies for JRth-2 at the amino acid level were 83% to barley leaf thionins DB4 (Bohlmann and Apel, 1987), 71% to pKG1940 (Gausing, 1987), 46% to the hordothionin Hth-l (Rodriguez-Palenzuela et 01., 1988) and purothionin Pur-AI (Ohtani et 01., 1977), 41% to crambin Thi2CaI (Teeter et 01., 1981) and 33% to the viscotoxin Vis A3 (Samuelsson et 01., 1974). Like other thionin precursors, the putative rice thionin has an N-terminal domain characteristic of a signal peptide and an acidic C-terminal extension. In the expression studies, rice thionins mRNA were found to accumulate abundantly in endosperm and shoots only with a transcript size of around 600-700 bp. In both of these tissues, the expression of the thionin genes was strongly repressed by the exposure to light. Southern analysis showed that the rice thionin seemed to be coded by 1-2 genes.